STRATEGY FOR MANAGING WORKLOADS OF AIR TRAFFIC CONTROLLER AT PERUM LPPNPI - Ari Satria Saputra (Dinasti Publisher, 2020)
This study aims to analyze workload management strategies, constraints in workload management strategies and planning and development of air traffic integration workload management strategies at Perum LPPNPI. Research data is data collected from interviews, literature studies and data observations obtained from the directorate of operations of the Perum LPPNPI office and evaluation of air navigation over a period of years to years. This type of research is a qualitative descriptive study that has a complete picture of a phenomenon or event that occurs according to its purpose. The method used by researchers in analyzing data is data collection, data reduction, data display and conclusion. Subjects in this study were 5 (five) sources as officials on duty at Perum LPPNPI. The results of this study indicate that the air traffic workload management strategy at Perum LPPNPI is in fulfilling the number of human resources and needs, restructuring air space, managing ATFM (Air Traffic Flow Management), paying more attention to FRMS (Fatigue Risk Management System).